Green HPLC technique development for the simultaneous determination of the potential combination of Mirabegron and Tamsulosin - Eman A. Bahgat; Hanaa Saleh; Islam M. Darwish; Omar M El-Abassy (Scientific Reports)
Abstract Mirabegron and tamsulosin have recently been prescribed to men with overactive bladder for the treatment of benign prostatic hypertrophy. An efficient and environmentally friendly HPLC method was developed to accurately measure the levels of mirabegron and tamsulosin in both their pure form and in medication formulations. Full separation was achieved on an X-Bridge C18 column using a gradient elution of (The A mobile phase was a buffer solution containing 1 mL of trifluoroacetic acid and 3 mL of triethylamine in 1,000 milliliters of water, the pH of the solution was then adjusted to 3 using triethylamine and the B-mobile phase was acetonitrile). The chromatographic peaks were obtained at a wavelength of 220 nm. Mirabegron and tamsulosin were identified with retention time values of 2.4 min and 8.9 min, respectively. In the concentration ranges of 2.5–55 µg/mL for mirabegron and 5–110 µg/mL for tamsulosin, remarkable linearity was seen. The limits of detection for the two analytes were 0.28 and 0.55 µg/mL, respectively, and their R2 values were 0.9999. The new HPLC method was evaluated for its environmental friendliness using the Analytical GREEness (AGREE) metric. Furthermore, the suggested technique was considered practicable based on the evaluation conducted using the Blue Applicability Grade Index (BAGI) assessment. Both evaluation methods were quite successful, yielding scores of 0.52 and 80, respectively. Compared to the TLC-reported method, HPLC is the preferred choice for the separation of the two analytes due to its sensitivity.